Analysis of the Needs of Health Workers with Triangulation Techniques at Health Centers Accompanying South Sorong Regency - Ester M. Pongsituru; Arlin Adam; Sudirman Sanuddin (Studi Ilmu Manajemen dan Organisasi, 2024)
Purpose: To achieve the goals and working principles of health centers and health offices, the expertise and capacity of human resources are very important in diagnosing and overcoming problems so that they can achieve solutions to each task and function carried out by health centers. Methodology/approach: This research was conducted at the Metemani Health Center, South Sorong Regency, from April to June 2024. The qualitative method used in this study was designed to produce descriptive data consisting of written and spoken words derived from people and observed behaviors. The primary informants of the study were all employees at the Metemani Health Center, which amounted to 18 health workers, using the purposive sampling technique. Results/findings: Research at the Metemani Health Center shows a shortage of health workers, especially doctors, nutritionists, and pharmaceutical workers. The recruitment of health workers must be based on the analysis of the needs and fulfillment of the Minimum Personnel Standards in the agency. The Metemani Health Center has difficulty getting pharmacy staff, especially pharmacists, so this has an impact on the quality of services provided. The Head of the Health Center suggested the need for non-health workers to support administrative tasks. Limitations: Analyzing the needs of healthcare workers based on workload is essential for optimizing the performance and quality of service. Fatigue and work stress can have an impact on productivity and service quality. Contribution: The theoretical implications of this study underscore the importance of maintaining the recruitment of health workers based on the analysis of needs and fulfilment of the Minimum Standards of Personnel at Health Institutions.